Sarcastic Expressions and the Influence of Social Distance and Relative Power in The TV Series Friends - Shaula Noorhayu Shelldyriani; Aris Munandar (Lexicon, 2020)
This research aims to identify and classify the sarcastic expressions found in the TV Series Friends. It applies the theory proposed by Camp (2011) which categorized sarcasm into four classes: Propositional, Lexical, Like-Prefixed, and Illocutionary Sarcasm. Considering sarcasm as a Face Threatening Act (FTA), it also analyzes the influence of relative power and social distance to see how these two social variables influence the delivery of sarcastic expressions. The findings show that Illocutionary Sarcasm is the most frequently used class of sarcasm with 30 utterances (45%) followed by Propositional Sarcasm which consists of 25 utterances (37%), Lexical Sarcasm with 10 utterances (15%) and lastly Like-Prefixed Sarcasm that have 2 utterances (3%). With Illocutionary and Propositional Sarcasm are known to be the most straightforward class of sarcasm, the results also show that these two classes of sarcasm are mainly used when the social distance (D) is negative where the interlocutors does not have the obligation to be polite due to their close intimacy. In cases where the social distance has positive value, the value of power (P) helps to determine which class of sarcasm is used. Furthermore, a clear context and common ground is essential to help identify sarcastic expressions and the intention underlying it.